Characteristics of Child Sexual Assault Within a Child Advocacy Center Client Population. Issue 1 (January 2015) - Carlson, Faye M.; Grassley, Jane; Reis, Janet; Davis, Kelley
Abstract : Abstract: This descriptive study summarized data from a child advocacy center to illustrate how such information might be used to profile the scope and character of child sexual abuse (CSA) at the community level. This detailed information is not available from national or state data but is needed to understand the circumstances of the children receiving services and the type of care they may need. Variables included victim demographics, type of sexual abuse and relationship to the perpetrator, and the person to whom the victim was most likely to disclose their sexual assault. A total sample of 841 case reports was reviewed. Chi-square tests were used to determine if there were statistically significant associations between the age groupings, type of abuse, and the perpetrator according to age grouping. Those children most often seen at this child advocacy center were girls (73%); White (67%); and living with their mothers, with both parents, or with parent and stepparent (80%). The incidence of CSA increased for girls across age groups. However, boys aged 6–10 years comprised the greatest percentage of the male sample (56%) who experienced CSA. For all three age groups, over half of the perpetrators were identified as relatives. Most children (85%) experienced high-impact sexual abuse behaviors of fondling, penetration, or some combination thereof. Children most often disclosed CSA to their mothers. Understanding patterns of CSA at the local level provides guidance beyond national and state data to forensic nurses regarding child and family needs within their communities.